2018
DOI: 10.3389/fneur.2018.01023
|View full text |Cite
|
Sign up to set email alerts
|

Is Mossy Fiber Sprouting a Potential Therapeutic Target for Epilepsy?

Abstract: Mesial temporal lobe epilepsy (MTLE) caused by hippocampal sclerosis is one of the most frequent focal epilepsies in adults. It is characterized by focal seizures that begin in the hippocampus, sometimes spread to the insulo-perisylvian regions and may progress to secondary generalized seizures. Morphological alterations in hippocampal sclerosis are well defined. Among them, hippocampal sclerosis is characterized by prominent cell loss in the hilus and CA1, and abnormal mossy fiber sprouting (granular cell axo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
56
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 59 publications
(62 citation statements)
references
References 194 publications
5
56
0
Order By: Relevance
“…Indeed, neurogenesis was substantially reduced, and a portion of newly born neurons continued to migrate into the dentate hilus in CERs, a feature also noted in previous KA models [32,39]. Also, an abnormal synaptic reorganization was observed in the form of aberrant mossy fiber sprouting into the dentate inner molecular layer, which is a form of plasticity that increases connectivity between dentate granule cells, and likely also contributes to persistent hyperexcitability in the DG [57,[59][60]. Also, CERs generated in this study exhibited anhedonia, which is a symptom of depression where activities that bring pleasure in normal conditions are no longer pleasurable (i.e., hyposensitivity to happiness).…”
Section: Discussionmentioning
confidence: 60%
See 1 more Smart Citation
“…Indeed, neurogenesis was substantially reduced, and a portion of newly born neurons continued to migrate into the dentate hilus in CERs, a feature also noted in previous KA models [32,39]. Also, an abnormal synaptic reorganization was observed in the form of aberrant mossy fiber sprouting into the dentate inner molecular layer, which is a form of plasticity that increases connectivity between dentate granule cells, and likely also contributes to persistent hyperexcitability in the DG [57,[59][60]. Also, CERs generated in this study exhibited anhedonia, which is a symptom of depression where activities that bring pleasure in normal conditions are no longer pleasurable (i.e., hyposensitivity to happiness).…”
Section: Discussionmentioning
confidence: 60%
“…Both TLE patients and animals that experienced SE have consistently shown abnormal sprouting of axons of dentate granule cells into the inner molecular layer of the DG, a process known as aberrant mossy fiber synaptic reorganization. Such sprouting of mossy fibers increases the connectivity between granule cells and may increase the propensity for generating SRS [57][58][59][60][61]. We examined the occurrence of mossy fiber sprouting using ZnT3 immunostaining, which demonstrated the presence of aberrant mossy fiber sprouting in the dentate supragranular layer of CERs (Fig.…”
Section: Aberrant Mossy Fiber Sprouting In the Dg Of Cersmentioning
confidence: 99%
“…For instance, the epileptic group presents a recovery in the SV2A levels during the latent phase (3 to 6 days post-SE) in four of the six regions: the amygdala, the striatum, the thalamus, and the hypothalamus. Such a recovery may be due to different compensatory processes taking place in response to SE, such as neurogenesis or synaptic reorganization [45,46], and seems to be accompanied by the reabsorption of the oedema which appears in temporal regions during the acute phase, as we can observe in the MRI images.…”
Section: Discussionmentioning
confidence: 60%
“…Traditionally, it was accepted that mossy fiber sprouting contributes robustly to the hyperexcitability of the hippocampus, but this pro-epileptogenic role has been questioned recently by Cavarsan et al because its presence is not necessary to develop MLTE. Despite the controversy concerning whether aberrant sprouting may be a cause or a consequence of the seizures, it seems likely that the rearrangement of neuronal circuitry observed in epileptic hippocampi implies the participation of certain guidance molecules in the process [111]. In 2003, Holtmaat et al observed that after induction of status epilepticus, Sema3A was temporarily downregulated in the entorhinal cortex, the main afferent of dentate gyrus, prior to the appearance of mossy fiber sprouting, suggesting that its downregulation could facilitate the formation of recurrent projections of mossy fibers after seizures [112].…”
Section: Involvement Of Semaphorins In Neuronal Disordersmentioning
confidence: 99%